Philo of Alexandria An annotated bibliography 1937-1986 - Radice, Roberto (Vigiliae Christianae, Supplements, 1988)
The first author in which the traditions of Judaic thought and Greek philosophy flow together in a significant way is Philo of Alexandria.This study presents a detailed and comprehensive examination of Philo's knowledge and utilization of the most popular philosophical work of his day, the Timaeus of Plato. A kind of "commentary" is given on all passages in Philo's oeuvre in which the Timaeus is used or referred to, followed by a "synthetic" account of the influence that it had on Philo's thought.; Readership: